BERBAGAI SIKAP DAN TANGGAPAN MASYARAKAT TENTANG PILKADA - J.Q.M Judantoro (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The Legisiative and Presidential Elections have given good lesson to Indonesian people, because it goes smoothly and without violence and but it is 1101 the case for the Regional Leaders Election since it has many problem oftenaccompanied with violence. This research is aimed to picture people's reaction and attittude about this went qualitatitive-descriptive research. approachthrough library research or more spscificly desk-research. The Result of this research is that The Office, Electoral s Committee (KPU),and the religious-leaders should give political education.to the people, underline the good morality and sportivity, so that the constituent could received the condition of the candidates whether they win or loose.